Nicotine inhibits firing activity of dorsal raphe 5-HT neurones in vivo. - Engberg, G; Erhardt, S; Sharp, T; Hajós, M (2000)
It is established that the brain monoaminergic systems are among the main targets of several dependence-inducing drugs, including nicotine. In the present study extracellular electrophysiological recordings were performed to investigate the effects of nicotine on dorsal raphe 5-HT neurones. Nicotine, administered systemically (50-400 microg/kg, i.v.) in chloral hydrate-anaesthetised rats, induced a transient inhibition of the majority of 5-HT neurones recorded (38 of 45). The inhibition was rapid in onset (about 30 s) and the firing rate returned to baseline within 1-3 min. No apparent tachyphylaxis was observed to this inhibitory effect. The centrally acting nicotine antagonist mecamylamine (4 mg/kg, i.v.), but not the peripherally acting nicotine antagonist chlorisondamine (0.3 mg/kg, i.v.) antagonised the nicotine-induced inhibition of 5-HT neurones. The inhibition of 5-HT neurones was also blocked with a selective 5-HT1A receptor antagonist (WAY 100635; 0.1 mg/kg, i.v.), indicating a possible involvement of somato-dendritic 5-HT1A receptors in the effect of nicotine. Interestingly, microiontophoretic application of nicotine into the dorsal raphe failed to inhibit 5-HT neurones, suggesting an indirect effect of nicotine on 5-HT neurones, possibly involving afferent pathways.